2020
DOI: 10.1155/2020/8843084
|View full text |Cite
|
Sign up to set email alerts
|

Application of Distributed Parameter Model to Assessment of Glioma IDH Mutation Status by Dynamic Contrast-Enhanced Magnetic Resonance Imaging

Abstract: Previous studies using contrast-enhanced imaging for glioma isocitrate dehydrogenase (IDH) mutation assessment showed promising yet inconsistent results, and this study attempts to explore this problem by using an advanced tracer kinetic model, the distributed parameter model (DP). Fifty-five patients with glioma examined using dynamic contrast-enhanced imaging sequence at a 3.0 T scanner were retrospectively reviewed. The imaging data were processed using DP, yielding the following parameters: blood flow F, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…This observation is in accordance with recent studies highlighting the importance of the initial components of the signal time-intensity curve for IDH status determination [34]. Signal deviation in these regions correlates to predictable vascularity phenotypes of IDH-mutant and IDH-wildtype tumors [35], as determined by IDH-specific vascular gene signatures [36]. Specifically, Choi et al [34] demonstrated that the curve components between T_0 and T_max performed best for the identification of IDH-mutant versus IDH-wildtype gliomas by applying an explainable recurrent neural network to attribute attention weights to specific parts of the T2* signal time-intensity curve.…”
Section: Performance Of Idh Status Prediction and Informative Radiomics Featuressupporting
confidence: 92%
“…This observation is in accordance with recent studies highlighting the importance of the initial components of the signal time-intensity curve for IDH status determination [34]. Signal deviation in these regions correlates to predictable vascularity phenotypes of IDH-mutant and IDH-wildtype tumors [35], as determined by IDH-specific vascular gene signatures [36]. Specifically, Choi et al [34] demonstrated that the curve components between T_0 and T_max performed best for the identification of IDH-mutant versus IDH-wildtype gliomas by applying an explainable recurrent neural network to attribute attention weights to specific parts of the T2* signal time-intensity curve.…”
Section: Performance Of Idh Status Prediction and Informative Radiomics Featuressupporting
confidence: 92%
“…DCE studies assessing the permeability parameters also showed potential for distinguishing between the two molecular entities. IDHmut gliomas were found to exhibit decreased CBF, volume transfer constant between blood plasma and extravascular extracellular space (Ktrans), blood plasma fractional volume (Vp), extravascular extracellular volume fraction (Ve), and area under the curve (AUC) [ 11 , 41 , 42 ]. With respect of ASL-CBF, some authors like Brendle et al and Yoo et al reported it to be useful to distinguish between these two subgroups [ 43 , 44 ], while others found only a moderate correlation [ 12 ].…”
Section: Clinical Applications Of Hemodynamic Imaging In Gliomas—partmentioning
confidence: 99%
“…Classical TK models such as EXTOFTS have been used to distinguish between benign and malignant STTs [ 13 15 ]. However, these two models are limited by using only a single constant transfer parameter (K trans ) to model transport, and thereby cannot distinguish between the transport of tracer molecules in blood vessels and the exchange process of tracer molecules between blood vessels and tissues [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced pharmacokinetic models, such as CC, ATH, and DP, have been proposed, providing a more accurate explanation of tracer transport in the tissue microenvironment, and rendering derived parameters that better describe the tumor tissue microenvironment [ 9 , 11 , 16 , 17 ]. These three models are concerned with two transport processes: intravascular perfusion of tracer molecules, and osmotic exchange inside and outside the vessel through the vessel wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation